Do Financial Ratios Send Value-Relevant Signals in Sharia Markets? (Evidence from IDX Sharia Growth) - Marpaung, Arif Pratama; Fadhillah, Rizka; Radiman, Radiman (Journal of International Conference Proceedings, 2025)
This study aims to empirically examine the effect of financial performance indicators on firm value in companies listed on the IDX Sharia Growth Index during the 2021–2023 period. Specifically, the research investigates whether Liquidity, Leverage, Profitability, Asset Growth, and the Investment Opportunity Set individually and simultaneously influence firm value, as measured by Price to Book Value (PBV). The sample consists of 30 companies consistently listed in the IDX Sharia Growth Index, observed over a three-year period, resulting in 90 firm-year observations. Data were collected using the documentary method, drawing from secondary sources such as financial statements and IDX official reports. Panel data regression analysis was employed using EViews 10 as the data processing tool. The findings reveal that Leverage, Profitability, and the Investment Opportunity Set have a significant positive effect on firm value. Conversely, Liquidity and Asset Growth do not show a statistically significant influence. Moreover, all five variables simultaneously have a significant effect on firm value. These results highlight the importance of financial structure, operational efficiency, and growth expectations in determining firm value, particularly within the context of sharia-compliant firms.